Analisis Komoditas Unggulan Tanaman Pangan Di Kabupaten Aceh Timur - Agustina Arida; M Mujiburrahmad; Syamsul Anwar (LPPM Universitas Malikussaleh – Indonesia, 2019)
Government efforts for agricultural development in order to increase economic growth in the current era of globalization aims to identify superior commodities that exist in the region. Thus, the government can increase competitiveness with other regions that produce the same commodity. The existence of superior commodities in an area reflects to agricultural resources and economic potential that can be further developed to increase regional economic growth. The purpose of this study is to find what superior commodities to food crops are and to determine the growth rate of production of food crops in East Aceh Regency. This study used LQ (Location Quotient) analysis and Compounding Factor Growth Analysis. The scope of this research is limited to the production and planting area of food crops (rice, corn, soybeans, peanuts, green beans, cassava, sweet potatoes) in East Aceh Regency. The types of data in this study are secondary data with the type of data time series production and planting area of food crops in East Aceh Regency during from 2012 to 2016. There were 7 (seven) food crop commodities found in East Aceh Regency, two commodities that have advantages (LQ> 1), namely rice and soybeans. Both commodities are classified as superior commodities because they are influenced by factors in the amount of planting area and high production. The area of planting and production of the two commodities contributed to the planting area and production of the Aceh Province exceeding the contribution of the same planting area and production of commodities in other regions. For soybean commodities, the value of LQ obtained from the planting area is (1.59) and the production LQ is equal to (1.63). While the LQ rice planted area obtained is (1.01) and the production LQ is equal to (1.05). The average of the leading commodities that get the first rank are soybean commodities with an average LQ value of (1.59) and the second rank is rice commodities with an average LQ value of (1.05). In East Aceh District there were two leading commodity that have an average growth rate of production above the rate of growth of Aceh Province are soybeans with an average growth rate of production of (10.50). Whereas rice with an average production growth rate of (-2.88). The average growth rate of rice production in East Aceh Regency is below the average growth rate of rice production in Aceh Province.